2015
DOI: 10.1186/s13054-015-0949-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse alveolar damage associated mortality in selected acute respiratory distress syndrome patients with open lung biopsy

Abstract: IntroductionDiffuse alveolar damage (DAD) is the pathological hallmark of acute respiratory distress syndrome (ARDS), however, the presence of DAD in the clinical criteria of ARDS patients by Berlin definition is little known. This study is designed to investigate the role of DAD in ARDS patients who underwent open lung biopsy.MethodsWe retrospectively reviewed all ARDS patients who met the Berlin definition and underwent open lung biopsy from January 1999 to January 2014 in a referred medical center. DAD is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 37 publications
7
87
1
4
Order By: Relevance
“…In our study we found postoperative complications in 30% of patients, mainly in the forms of bleeding and air leak. A specific diagnosis was found in greater than 50% of patients in all studies except for four studies which had rates in the 40% range [6, 7, 9, 11]. Treatment was altered in more than 50% of patients for 14 of the 18 studies.…”
Section: Discussionmentioning
confidence: 90%
“…In our study we found postoperative complications in 30% of patients, mainly in the forms of bleeding and air leak. A specific diagnosis was found in greater than 50% of patients in all studies except for four studies which had rates in the 40% range [6, 7, 9, 11]. Treatment was altered in more than 50% of patients for 14 of the 18 studies.…”
Section: Discussionmentioning
confidence: 90%
“…However, a clinical diagnosis of ARDS does not necessarily coincide with the presence of DAD, the histological hallmark of the syndrome, suggesting the heterogeneity of this clinical condition (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…(10) However, all of these differences do not exclude the possibility that some physiopathological pathways may be present in both entities and might explain why some pharmacological treatments may improve both conditions (see below).…”
Section: Introductionmentioning
confidence: 99%